PERFORMANCE OF INDONESIAN HIGHER EDUCATION UNDER THE INFLUENCE OF ORGANIZATIONAL CULTURE AND LECTURER PERFORMANCE - Dewi Suma; Budi Alamsyah Siregar (UPMI Management, 2022)
The study aims to see the role of organizational culture and lecturer performance in improving university organizational performance. We use the inferential verification technique, which is a strategy used by researchers to assess the validity of the hypotheses presented by collecting actual data from several higher education administrators. Two hundred samples from higher education institutions in Indonesia were deliberately selected as respondents. We used Structural Equation Modeling (SEM) analysis to test the hypotheses, aided by Smart-PLS software. Based on the research findings, it can be concluded that organizational culture has a significant positive effect on the performance of higher education organizations, lecturer performance has a significant positive effect on higher education organizational performance, and organizational culture has a significant positive effect on the performance of college lecturers. The limitation of this research is that the survey only focuses on universities in Indonesia and the tactical management level of an organization. Practical implications: According to research findings, improving lecturer performance and organizational culture can improve the organizational performance of tertiary institutions in Indonesia. The lecturer performance variable is proven to be a mediating or intervening variable for organizational culture influencing the performance of higher education organizations in Indonesia. Based on the 1945 Constitution, education, including higher education in Indonesia, is one of the indicators of advancing science and technology, higher education must be the driving force of national development, and higher education solves the nation's problems. JEL Classification: M10, M12, O15